UN MODULE D'EXAMEN CLINIQUE OBJECTIF STRUCTURÉ (ECOS) INTERACTIF POUR ÉVALUER LE RENDEMENT EN ANATOMIE PATHOLOGIQUE. - Diaconescu, Elena Diana; Salagean, Alex O.; Tawedrous, Eriny; Mirham, Lorna; Krizova, Adriana; Faragalla, Hala; Sade, Shachar; Bullock, Martin; Grin, Andrea; Streutker, Catherine; Carter, Beverley; Lee, Mark; et al. (Canadian Journal of Pathology, 2018)
Introduction: Approaching a new era of precision medicine, the role of the pathologist is evolving from being a diagnostician to becoming an active participant in patient management. Pathology resident assessment should be able to evaluate background knowledge, ability to reach the correct diagnosis on glass slides, and case management ability. The latter is usually captured by oral or written examinations. Problems associated with an oral exam include potential variability/inconsistency in question delivery/phrasing for both examiner and examinee and also the variability in delivery/interpretation of the answers, in addition to cost and stress. Methods: A computer application for resident performance assessment in anatomical pathology was developed. The web-based oral examination simulator can efficiently examine residents on a broad range of subjects and skills in a reliable and standardized manner. Scenarios were programmed, each representing a "theme" that can be used as a stand-alone module. The application can test knowledge in grossing techniques, microscopy, ancillary studies, clinical knowledge, quality assurance, and ethical considerations. Results: Examinees were allowed to interact in real-time with digital histological slides and digitalized gross specimens, thus simulating real-life situations. The module incorporates various levels of testing for clinical information including radiological images, immunohistochemical slides and interactive grossing sections. Question styles included multiple choice questions, mix and match, free-text and decisiontree type questions. The system accommodates equivalent terminologies and minor spelling mistakes. Conclusions: In the future, a trial study including multiple academic centers to test the utility and ease of use of the computer-based application could be created.